2002
DOI: 10.1177/1468018102002001094
|View full text |Cite
|
Sign up to set email alerts
|

The Internationalization of Long Term Care Provision

Abstract: This article analyses the extent and form of internationalization of the three largest for-profit providers of long term nursing and residential care for older people in the UK. This is a departure from most contributions to the analysis of the relationship between globalization and welfare, which have been focused at the level of the nation state. In focusing upon internationalized providers of welfare services, the article borrows from other disciplines such as international business studies. All three firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
0
16
0
2
Order By: Relevance
“…Commodifying trends have accelerated the intervention of the private market in health and social care and made care big international business. For example in long term care, British United Provident Association has operations in Spain, Ireland, Thailand, Hong Kong and Saudi Arabia (Holden, 2002). A fourth dynamic is national and international political contestations over defining how care and health needs should be met.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Commodifying trends have accelerated the intervention of the private market in health and social care and made care big international business. For example in long term care, British United Provident Association has operations in Spain, Ireland, Thailand, Hong Kong and Saudi Arabia (Holden, 2002). A fourth dynamic is national and international political contestations over defining how care and health needs should be met.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The third sector or community also increasingly provides a social reproductive function, although how it supports the reproductive sectors, such as personal services and health, is less well specified. Finally, the marketisation of social reproduction has increased and become big business (Holden 2002;Lethbridge 2011;Williams 2011). …”
Section: Welfare Regimesmentioning
confidence: 99%
“…The vast majority of the literature has focused on specific case studies, rather than accounting for the actual magnitude of internationalisation taking place through this mode of supply. In these studies, the United States has been regarded as an important source country for health care service firms establishing abroad, in particular in Latin America and the United Kingdom (Holden 2002;Jasso-Aguilar, Waitzkin et al 2004). One particular study of the United Kingdom found that 22% of all independent hospital beds were owned by the United States (Mohan 1991: 857 cited in Holden 2002).…”
Section: What Is It?mentioning
confidence: 99%
“…In these studies, the United States has been regarded as an important source country for health care service firms establishing abroad, in particular in Latin America and the United Kingdom (Holden 2002;Jasso-Aguilar, Waitzkin et al 2004). One particular study of the United Kingdom found that 22% of all independent hospital beds were owned by the United States (Mohan 1991: 857 cited in Holden 2002). According to a study using the Fortune Global 500 list for 2002 as a single year, direct health services providers were the least internationalised, while producers of goods were the most internationalised (Holden 2005 activities of foreign companies established in the host country, including export, import, sales, turnover and employment.…”
Section: What Is It?mentioning
confidence: 99%